Comparative analysis of an off-grid PV system for different types of batteries - Raff, Rebeka (Array, 2018)
The aim of this paper is to find an optimal size of different components of an off-grid PV system in the HOMER software with different types of batteries (lead-acid batteries and lithium-ion batteries). The proposed model shows the optimal size of the off-grid PV system for a holiday cottage with regard to eligibility criteria for various types of batteries and the net present cost (NPC). The observed off-grid PV system consists of PV modules, a load, a converter and batteries and it is modelled in the HOMER software. The load is modelled with a daily load diagram for the holiday cottage. For lead-acid and lithium-ion batteries the optimal size of different components of an off-grid PV system for five different scenarios (in respect of the price and life-time) is obtained. In addition, the optimal size of the presented model with respect to different values of capacity shortage ranging from 0% to 5% is presented.